Mechanisms of BK Channel Activation by Docosahexaenoic Acid in Rat Coronary Arterial Smooth Muscle Cells - Qian, Ling-Ling; Sun, Man-Qing; Wang, Ru-Xing; Lu, Tong; Wu, Ying; Dang, Shi-Peng; Tang, Xu; Ji, Yuan; Liu, Xiao-Yu; Zhao, Xiao-Xi; Wang, Wen; Chai, Qiang; et al. (Frontiers in Pharmacology, 2018)
Aims： Docosahexaenoic acid (DHA) is known to activate the vascular large-conductance calcium-activated potassium (BK) channels and have protective effects on the cardiovascular system. However, the underlying mechanisms through which DHA activates BK channels remain unclear. In this study, we determined such mechanisms by examining the effects of different concentrations of DHA on BK channels in freshly isolated rat coronary arterial smooth muscle cells using patch clamp techniques. Methods and Results： We found that BK channels are the major potassium currents activated by DHA in rat coronary arterial smooth muscle cells and the effects of DHA on BK channels are concentration dependent with a bimodal distribution. At concentrations of less than 1 μM, DHA activated whole-cell BK currents with an EC50 of 0.24 ± 0.05 μM and the activation effects were abolished by pre-incubation with SKF525A (10 μM), a cytochrome P450 (CYP) epoxygenase inhibitor, suggesting the role of DHA-epxoide. High concentrations of DHA (1-10 μM) activated whole-cell BK currents with an EC50 of 2.38 ± 0.22 μM and the activation effects were unaltered by pre-incubation with SKF525A. Single channel studies showed that the open probabilities of BK channels were unchanged in the presence of low concentrations of DHA, while significantly increased with high concentrations of DHA. In addition, DHA induced a dose-dependent increase in cytosolic calcium concentrations with an EC50 of 0.037 ± 0.01 μM via phospholipase C–inositol triphosphate–Ca2+ signal pathway, and inhibition of this pathway reduced DHA-induced BK activation. Conclusion： These results suggest that DHA can activate BK channels by multiple mechanisms. Low concentration DHA-induced BK channel activation is mediated through CYP epoxygenase metabolites, while high concentration DHA can directly activate BK channels. In addition, DHA at low and high concentrations can both activate BK channels by elevated cytosolic calcium through the phospholipase C–inositol triphosphate–Ca2+ signal pathway.